Prediction of Suicidal Ideation Based on Resilience, Self-Compassion, and Attachment Styles in Adolescent Girls - Yaqoubi Mamaghani , Rana; Abbasi Abrazgah, Mozhgan (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  The objective of this study was to predict suicidal ideation in adolescent girls based on resilience, self-compassion, and attachment styles.Methods and Materials: This descriptive–correlational study was conducted among adolescent girls attending public lower-secondary schools in District 16 of Tehran during the 2023–2024 academic year. A total of 239 participants who reported suicidal thoughts in psychological screening were selected through convenience sampling. Data were collected using the Multi-Attitude Suicide Tendency Scale (MAST), the Connor–Davidson Resilience Scale (CD-RISC), the Self-Compassion Scale–Short Form (SCS-SF), and the Revised Adult Attachment Scale (RAAS). Pearson correlation and simultaneous multiple linear regression analyses were performed using SPSS version 26 to examine associations and predictive relationships among the study variables.Findings: Correlation analysis showed that resilience (r = –.36), self-compassion (r = –.14), and secure attachment (r = –.19) were significantly and negatively associated with suicidal ideation, while avoidant (r = .32) and ambivalent/anxious attachment styles (r = .19) exhibited significant positive correlations (p < .05). Regression analysis revealed that the overall model significantly predicted suicidal ideation (F(5,232) = 12.56, p = .001), explaining 21% of the variance (R² = .21). Among the predictors, resilience (β = –.28, p = .001) and avoidant attachment (β = .24, p = .001) were significant predictors, whereas self-compassion, secure attachment, and ambivalent/anxious attachment were not significant predictors.Conclusion: The findings indicate that resilience and avoidant attachment style play significant roles in predicting suicidal ideation among adolescent girls, underscoring the importance of enhancing adaptive coping resources and addressing maladaptive attachment patterns in suicide prevention efforts targeting this population.